200k views
0 votes
Solve by completing the square

6x-x^2-7

User Jiemurat
by
5.0k points

2 Answers

4 votes

Answer:


x=\{3+\sqrt 2,\:\:3-\sqrt 2\}

Explanation:


6x-x^2-7=0\\x^2-6x +7=0\\x^2-2.3.x +3^2=3^2-7\\(x-3)^2=9-7\\\huge\boxed{(x-3)^2=2}...(square\: completed)\\x-3=\pm√(2) \\x=3+\pm√(2)\\\therefore x =3+√(2)\: or \: x =3-√(2)\\\therefore x =\{3+√(2),\:\:3-√(2)\}\\

User Dinari
by
5.2k points
4 votes
Hi there!

The completed square is -(x - 3) ^2 + 2

Hope this helps !
User Ctpanchal
by
5.2k points